Literature Review: Efektivitas Jambu Biji Merah terhadap Peningkatan Hemoglobin sebagai Upaya Pencegahan Anemia Ibu Hamil dan Remaja Putri - Nabiilah Faaizah Rahman (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Anemia is a common nutritional problem that occurs in vulnerable groups such as pregnant women and teenage girls. One of its main causes is iron deficiency, which can be exacerbated by low vitamin C intake. Red guava (Psidium guajava L.) is a local fruit that is rich in vitamin C and has the potential to improve iron absorption, thus supporting an increase in hemoglobin levels. This study aims to review the effectiveness of red guava in increasing hemoglobin as an effort to prevent anemia. This study uses a literature review design on five experimental research articles published in the last 10 years. The study results show that the consumption of red guava, whether consumed alone or in combination, can significantly increase hemoglobin levels in pregnant women and adolescent girls with anemia. The vitamin C content in red guava plays a role in enhancing the bioavailability of iron needed for hemoglobin formation. Thus, red guava has the potential to be used as part of a locally based food nutrition intervention that is effective, affordable, and applicable in the effort to prevent anemia.